PENJAMINAN UTANG PIUTANG DENGAN JAMINAN SERTIFIKAT RUMAH MILIK PENJAMIN OLEH PIHAK DEBITUR KEPADA KREDITUR - Herlina, Herlina; Sasongko, Satrio Gayo (SINERGI : Jurnal Riset Ilmiah, 2024)
This article aims to find out the mechanism of the guarantor of debts and receivables with the guarantee of a house certificate owned by the guarantor by the debtor to the creditor or savings and loan cooperative agreement between the guarantor and the debtor on the land certificate that is collateralized for reasons in the form of unwritten, trust and length of the agreement between the parties debtor by the creditor for 5 years from or since the signing of the agreement from 2023 to 2027 and the agreement is carried out in the South Tangerang Legal Area, more precisely at the place where the object is used as collateral which is located in Rempoa, East Ciputat District. This research is an empirical research that is descriptive. The data source used is primary data obtained through interviews with related parties and secondary data used are books, laws and regulations, journals and materials from the internet and other related sources. The data analysis technique used is qualitative with an interactive analysis model. Based on the results of the research on Debt and receivables guarantor with a guarantee of a house certificate owned by a guarantor by the debtor in the jurisdiction of South Tangerang, more precisely in the place of the object that is used as collateral which is located in Rempoa, East Ciputat District in the background with the interest of opening a thousand pempek business branches. The agreement process does not require difficult procedures, only based on trust